Experimental Investigation of Isothermal Section of the B-Cr-Fe Phase Diagram at 1353 K - Viera Homolová; Lucia Čiripová (Advances in Materials Science and Engineering)
The isothermal section of the B-Cr-Fe ternary system was studied experimentally at 1353 K. X-ray diffraction and scanning electron microscopy equipped with EDX analyzer were used for determination of phase equilibria and composition of the coexisting phases in the B-Cr-Fe model alloys after long-term annealing (1500–2205 h). Two iron borides FeB and Fe2B, six chromium borides Cr2B, Cr5B3, CrB, Cr3B4, CrB2, and CrB4 and also iron and chromium solid solutions (α(Fe,Cr), α(Cr,Fe), γ(Fe,Cr)) and β-rhombohedral B were observed in the alloys. High solubilities of the third element in binary borides and no ternary phase were found. Based on the experimental results, isothermal section of the B-Cr-Fe system at 1353 K was determined.